A role for TENM1 mutations in congenital general anosmia. Issue 3 (31st May 2016) - Alkelai, A.; Olender, T.; Haffner‐Krausz, R.; Tsoory, M.M.; Boyko, V.; Tatarskyy, P.; Gross‐Isseroff, R.; Milgrom, R.; Shushan, S.; Blau, I.; Cohn, E.; Beeri, R.; et al.
Abstract : Congenital general anosmia (CGA) is a neurological disorder entailing a complete innate inability to sense odors. While the mechanisms underlying vertebrate olfaction have been studied in detail, there are still gaps in our understanding of the molecular genetic basis of innate olfactory disorders. Applying whole‐exome sequencing to a family multiply affected with CGA, we identified three members with a rare X‐linked missense mutation in the TENM1 ( teneurin 1 ) gene (ENST00000422452:c.C4829T). In Drosophila melanogaster, TENM1 functions in synaptic‐partner‐matching between axons of olfactory sensory neurons and target projection neurons and is involved in synapse organization in the olfactory system. We used CRISPR‐Cas9 system to generate a Tenm1 disrupted mouse model. Tenm1 −/− and point‐mutated Tenm1 A /A adult mice were shown to have an altered ability to locate a buried food pellet. Tenm1 A /A mice also displayed an altered ability to sense aversive odors. Results of our study, that describes a new Tenm1 mouse, agree with the hypothesis that TENM1 has a role in olfaction. However, additional studies should be done in larger CGA cohorts, to provide statistical evidence that loss‐of‐function mutations in TENM1 can solely cause the disease in our and other CGA cases. Abstract :